Momento de dipolo elétrico do nêutron no modelo 3-3-1 - Santos, George De Conto [UNESP] (2014)
We analyse the neutron electric dipole moment in the 3-3-1 model with heavy leptons. We compare the theoretical predictions of this model with the actual experimental limits and give limits to some of its parameters